2018
DOI: 10.3389/fpsyg.2018.02626
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Comparison on Subjective Well-Being of Kindergarten Teachers: Hong Kong and Italy

Abstract: Background: Teachers’ subjective well-being (SWB) has received much attention, in the light of the major increase in sick leave as well as job quitting among teachers across different cultures and countries. Studies on SWB of kindergarten teachers are still scarce, since most of the academic literature is focused on teachers of primary and secondary schools.Aims: The purpose of this study was to analyze and compare kindergarten teachers’ SWB in Hong Kong and Italy.Methods: 367 Hong Kong and 243 Italian kinderg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Finally, and most germane for the present paper, the representation of the network of association (i.e., total, direct, and indirect effects) in an integrated structural model supported the theoretical viewpoints [ 63 ] considering subjective happiness, work engagement, and environmental working condition (and fit) as dynamically shaping the social endeavor in which kindergarten teachers are involved during their daily profession. It must be stated here that, in adopting the term “expected effects,” we referred to the assessment of direct natural effects [ 63 ], which allows for natural variation between subjects in the level of the target variables rather than interpreting a direct effect from the lens of causality framework. With regard to indirect effects between considered variables, no specific hypotheses were formulated.…”
Section: Introductionsupporting
confidence: 71%
“…Finally, and most germane for the present paper, the representation of the network of association (i.e., total, direct, and indirect effects) in an integrated structural model supported the theoretical viewpoints [ 63 ] considering subjective happiness, work engagement, and environmental working condition (and fit) as dynamically shaping the social endeavor in which kindergarten teachers are involved during their daily profession. It must be stated here that, in adopting the term “expected effects,” we referred to the assessment of direct natural effects [ 63 ], which allows for natural variation between subjects in the level of the target variables rather than interpreting a direct effect from the lens of causality framework. With regard to indirect effects between considered variables, no specific hypotheses were formulated.…”
Section: Introductionsupporting
confidence: 71%
“…Unsatisfactory support was found to be associated with higher emotional exhaustion in Italian teachers compared to Swiss teachers (Fiorilli et al, 2015). In other studies, Hong Kong teachers demonstrated that their higher job satisfaction was linked to their wages and promotion, while Italian teachers demonstrated greater satisfaction from supervision, work conditions, relationships with coworkers, the network of work, and communication (Benevene et al, 2018). This can be interpreted to explain why social support plays a much more important role for Italian teachers than Swiss teachers (Avanzi et al, 2018), as Italian teachers can be more vulnerable to stress due to lower salaries and more restrictions on career advancement than teachers in other European countries (Benevene et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Although these are the main variables that induce organizational commitment, once teacher efficacy and CSES become the sole emphases, the variables may conversely lead to job demands that degrade morale and commitment by attributing the success or failure of organizational commitment to either individual teachers or the organization. Although the job resources required by each individual may differ, promotion, reward, compensation (Eberts et al, 2002; Benevene et al, 2018), social support, autonomy, and performance feedback (Taris and Feij, 2004; Salanova et al, 2005; Bakker and Demerouti, 2007) generally lead to a synchronization process. Among these resources, social support displays realistic significance for the organization’s health.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the literature on the teachers' well-being in the school context, and in particular in the Early Childcare and Education Centers, shows a rather fragmented framework of data and empirical models (Hall-Kenyon et al, 2014;De Stasio et al, 2017;Benevene et al, 2018). The studies specifically show that the well-being construct has been described in different terms by different authors (Bowling et al, 2010;Hall-Kenyon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The studies specifically show that the well-being construct has been described in different terms by different authors (Bowling et al, 2010;Hall-Kenyon et al, 2014). It can be noted that most of the research had focused on the individual dimensions that contribute to the teachers' well-being, such as emotional competence, temperament, self-esteem, educational qualifications, and years of professional experience (Hall-Kenyon et al, 2014;De Stasio et al, 2017;Benevene et al, 2018).…”
Section: Introductionmentioning
confidence: 99%